2018
DOI: 10.1142/s0129054118410010
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms and Bounds for L-Drawings of Directed Graphs

Abstract: We introduce L-drawings, a novel paradigm for representing directed graphs aiming at combining the readability features of orthogonal drawings with the expressive power of adjacency matrix representations. In an L-drawing, vertices have exclusive [Formula: see text]- and [Formula: see text]-coordinates and edges consist of two segments, one exiting the source vertically and one entering the destination horizontally. We study the problem of computing L-drawings using minimum ink. We prove its NP-hardness and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…They are called rook-drawings when the edges are straight lines 58,59 and L-drawings when the edges have an orthogonal L-shape, that is, when each edge consists of exactly a vertical segment and a horizontal segment. 11 Our 2D drawing model will be called cc-L-drawing , because it is an L-drawing with rectangular regions that enclose the different connected components. Note that, since no vertices share the same x -coordinate or the same y -coordinate, an L-shaped edge in the drawing can always be added without intersecting any vertex, except its end-vertices.…”
Section: Models Metrics and Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are called rook-drawings when the edges are straight lines 58,59 and L-drawings when the edges have an orthogonal L-shape, that is, when each edge consists of exactly a vertical segment and a horizontal segment. 11 Our 2D drawing model will be called cc-L-drawing , because it is an L-drawing with rectangular regions that enclose the different connected components. Note that, since no vertices share the same x -coordinate or the same y -coordinate, an L-shaped edge in the drawing can always be added without intersecting any vertex, except its end-vertices.…”
Section: Models Metrics and Algorithmsmentioning
confidence: 99%
“…We describe two different visualization models and related online algorithms, one for the 1-dimensional space and the other for the 2-dimensional space. The 1-dimensional visualization model adopts an arc diagram style, 10 while the 2-dimensional model exploits a variant of orthogonal drawings , 11,12 that is, drawings whose vertices are mapped to points of an integer grid and edges are drawn as chains of horizontal and vertical segments. In both models the connected components are regarded as clusters and are drawn inside rectangular regions.…”
Section: Introductionmentioning
confidence: 99%
“…Assume first that T has a source s, a sink t and an in/out-vertex w. There are three cases: (1) The angles in T at s and t, respectively, are both 0 • (Fig. 18), ( 2) the angle at either the source or the sink -say the source -is 0 • (Fig.…”
Section: E Planar 3-treesmentioning
confidence: 99%
“…1(c)). Non-planar L-drawings were first defined by Angelini et al [1]. Chaplick et al [10] showed that it is NP-complete to decide whether a directed graph has a planar L-drawing if the embedding is not fixed.…”
Section: Introductionmentioning
confidence: 99%
“…4-modal embeddings, where the outgoing and the incoming edges at each vertex form up to four disjoint sequences with alternating orientations, arise in the context of planar L-drawings of digraphs. In an L-drawing of an n-vertex digraph, introduced by Angelini et al [1], vertices are placed on the n × n grid so that each vertex is assigned a unique x-coordinate and a unique y-coordinate and each edge uv (directed from u to v) is represented as a 1-bend orthogonal polyline composed of a vertical segment incident to u and of a horizontal segment incident to v. Recently, Chaplick et al [13] addressed the question of deciding the existence of planar L-drawings, i.e., L-drawings whose edges might possibly overlap but do not cross and observe that the existence of a 4-modal embedding is a necessary condition for a digraph to admit such a representation (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%